2020
DOI: 10.1037/edu0000405
|View full text |Cite
|
Sign up to set email alerts
|

Can a brief, digital skill training intervention help undergraduates “learn to learn” and improve their STEM achievement?

Abstract: Students who drop out of their science, technology, engineering, and math (STEM) majors commonly report that they lack skills critical to STEM learning and career pursuits. Many training programs exist to develop students’ learning skills and they typically achieve small to medium effects on behaviors and performance. However, these programs require large investments of students’ and instructors’ time and effort, which limits their applicability to large lecture course formats commonly employed in early underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 38 publications
7
67
0
Order By: Relevance
“…More substantive interventions have provided more reliable outcomes with young adults. Researchers studying college students have had success with a 2-h online training that required limited instructor intervention (Bernacki, Vosicka, & Utz, 2019). There is evidence that a semester-long intervention that incorporates instructor modeling can improve beliefs about learning and the use of SRL strategies such as elaboration (Muis & Duffy, 2013).…”
Section: Changing Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…More substantive interventions have provided more reliable outcomes with young adults. Researchers studying college students have had success with a 2-h online training that required limited instructor intervention (Bernacki, Vosicka, & Utz, 2019). There is evidence that a semester-long intervention that incorporates instructor modeling can improve beliefs about learning and the use of SRL strategies such as elaboration (Muis & Duffy, 2013).…”
Section: Changing Behaviormentioning
confidence: 99%
“…Subsequent research can augment this intervention with attributes that have demonstrated success in similar efforts (e.g., Bernacki et al, 2019;Nguyen et al, 2018). Increasing engagement in the intervention will be key and there are indications that some level of 'gamification' can support technology based interventions (Schindler, Burkholder, Morad, & Marsh, 2017).…”
Section: Interventionmentioning
confidence: 99%
“…Aside from these instructional methods, another important aspect of improving learning involves understanding how students manage their own independent learning time. A growing body of work finds that differences in college students' course outcomes are uniquely dependent on how students study (Bernacki et al 2019;Hartwig and Dunlosky 2012;Rodriguez et al 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Implementation science. Implementation science is related to, but distinct from, higher education-relevant cognitive psychology (e.g., Dunlosky et al 2013 ), science of learning (e.g., Halpern and Hakel 2003 ), educational psychology (e.g., Bernacki et al 2019 ), SoTL (e.g., Corral et al 2019 ), discipline-based educational research in psychology (e.g., National Research Council 2002 ), and the learning sciences (e.g., Sawyer and Dunlosky 2019 ). Implementation science builds on effectiveness research in applied settings—an existing evidence base is essential for designing implementation research studies (Lane-Fall et al 2019 ).…”
Section: A Framework For Moving Research Into Practice In Higher Educmentioning
confidence: 99%